Comparative genetic profiling aids diagnosis and clinical decision making in challenging cases of CUP syndrome - Bochtler, Tilmann; Endris, Volker; Leichsenring, Jonas; Neumann, Olaf; Volckmar, Anna-Lena; Kirchner, Martina; Allgäuer, Michael; Schirmacher, Peter; Krämer, Alwin; Stenzinger, Albrecht (International journal of cancer, 2019)
Cancer of unknown primary (CUP) denotes cancer cases where metastatic spread is histologically confirmed, but no respective primary tumor can be identified. The challenging diagnosis of CUP is further complicated in cases with previously identified malignancies or with dubious clonal relationship between metastatic sites due to ambiguous histology. Our study aims at elucidating clonal relationships by comparing the respective mutational spectra. Targeted next-generation sequencing (NGS) employing formalin-fixed and paraffin-embedded (FFPE) tumor tissue was performed on 174 consecutive CUP patients. Among these, 43/174 (24.7%) patients had a documented prior malignancy. Data on pairwise targeted NGS testing to address clonal relationships between the previous malignancy and the presumed CUP (n = 11) or between different CUP metastatic sites (n = 7) was available in 18 patients. NGS could clarify clonal relationships in 16/18 cases. Among the 11 CUP patients with antecedent malignancies, four cases were clonally independent of the previous malignancy but harbored deleterious germline mutations in BRCA/BAP1/ATM genes. Seven CUP cases were clonally related to the antecedent malignancy, changing the CUP diagnosis to relapse of the prior malignancy. In the seven CUP cases, with doubtfully related metastatic sites, NGS confirmed clonal relationship in five cases and was inconclusive in two. In conclusion, NGS proved an efficient tool to elucidate clonal relationships in clinically challenging CUP cases. Our study cautions against a premature diagnosis of CUP. Relapses of antecedent malignancies should be carefully considered. CUPs clonally independent from the antecedent malignancy should raise a red flag of a potential cancer-predisposing germline mutation.
Gesehen am 29.10.2019